Kinetic study of biomass hydrolysis under high pressure conditions - Relvas, Frederico Miguel Horta de Albuquerque Moura (2014)
This study was focused on the kinetics of lignocellulosic biomass pre-treatment, in particular CO2-assisted autohydrolysis. The temperature was fixed at 180 ºC, varying pressure from 0 (CO2-free autohydrolysis), 20, 35 to 50 bar. For every pressure, a set of isothermal reactions was performed for various reaction times from 0 and 45 minutes. The pre-treatment resulted in a liquid, solid and gas phases, which were analyzed by HPLC. The liquid phase is essentially composed by sugars both in oligomer and monomer forms, mainly from xylan, also containing acetic acid and degradation products such as furfural and formic acid. In turn, there was an improvement of lignin and glucan’s fraction in the solid residue, being more pronounced for longer treatments. Regarding gas phase collected during depressurization, no traces of products from biomass hydrolysis were found. Basing on the literature and experimental results, 4 kinetic models were developed to predict the behavior of the biomass hydrolysis. Models for xylan, arabinoxylan, glucan and another for acetyl groups were presented. According to the results, the use of CO2 is beneficial for the selective fractionation of biomass, including hemicellulose and amorphous cellulose fractions. Beside, CO2 favors the production of xylooligosaccharides (XOS) achieving a maximum concentration of 14.76 g·L-1 at 50 bar assay vs 13.62 g·L-1 in case of autohydrolysis. Furthermore the conversion of oligomers to monomers is directly proportional to pressure and is enhanced by CO2 presence. With respect to the developed kinetic models, all showed good correlation with experimental data, with R2 as high as 0.9986. In the worst case, the R2 was 0.7865 what considering the so complex multistep analysis process can be acknowledge as a good result. Despite kinetic constants showed an increase of hydrolysis rate of xylan and arabinan in the presence of CO2, they decreases for higher pressures used. In turn, the model for acetyl groups also shows very consistent results with the lowest R2 of 0.9491. The removal of acetyl groups seems to be impaired by the carbon dioxide presence. With respect to glucan, the obtained data shows that reactions are close to zero order as they are independent on the products’ concentrations.